Analysis of the impact of the shape and size of the absorber on the efficiency of solar collector operation (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article analyzes the influence of the shape and size of the absorber on the efficiency of solar collector operation. The purpose of this research is to identify the optimal absorber parameters that contribute to the maximum conversion of solar energy into thermal energy. The authors examine various geometric configurations of absorbers and assess their efficiency in the context of diverse climatic conditions. The research methodology includes theoretical analysis, modeling of heat exchange processes, and direct experimental study. The results demonstrate that the shape of the absorber significantly affects the efficiency of the collector, with larger absorbers providing better thermal gain but being subject to greater losses at low ambient temperatures. In conclusion, the authors emphasize the importance of considering local climatic conditions when designing and operating solar collectors and offer recommendations for selecting optimal absorber parameters for various applied scenarios.
Keywords: Solar collector, absorber efficiency, heat exchange, experimental studies, numerical modeling, climatic conditions, absorber materials, thermal inertia